Descredibilização da imprensa a partir de ataques misóginos: uma análise do Governo Bolsonaro em relação às mulheres jornalistas - Rambo, Mariane Carolina Packes (Universidade do Vale do Rio dos Sinos, 2024)
This research aims to understand which forms of attack occurred against female journalists and which meanings may be perceived from the attacks against Patrícia Campos Mello and Vera Magalhães during the Bolsonaro government. As methodological procedures, we utilize multiple cases study (YIN, 2015) and analysis of the construction of meaning in digital networks (AQUINO AND SCHUCH, 2022). From the analysis of cases and the theoretical framework, we perceive two forms of attacks against the journalists: 1) discrediting the journalist in her role and 2) attacking their reputation – aiming to corrupt their public image, both as “respectable” women (considering the patriarchal view of society) and also as serious and impartial professionals (calling them communists, for instance). About the perceived categories of meanings, there is criticism and compliments for both those who attacked and those who were attacked in the comments, e that also journalism in general is villainized by this group. Furthermore, we perceive that, in all attacks, other women were offended and aggressed, often utilizing the same argument and offense targeted to the female journalists.
Keywords: Jornalismo; Mulheres jornalistas; Gênero; Descredibilização; Bolsonaro; Journalism; Female journalists; Gender; Discredit; ACCNPQ::Ciências Sociais Aplicadas::Comunicação